Sedative and Anxiolytic Activities of Geodorum densiflorum Roots in Swiss Albino Mice - Mominur Rahman; Razibul Habib; Mohammed Aktar Sayeed; Muhammad Erfan Uddin; Rasheduzzaman Chowdhury; Mohammad A. Rashid; Amer Hasan; Mansoor Ahmed (Journal of Pharmacy and Nutrition Sciences, 2013)
Fresh root of Geodorum densiflorum (Lam.) (Orchidaceae) has applications in regularizing menstrual cycle and as topical aids in insect bites and wounds. The tuber extracts of some plants belonging to Geodorum have folkloric reputation in the management of transient anxiety. The current study was undertaken to investigate the sedative/ anxiolytic effects of G. densiflorum root extracts using rodent behavioral models, such as open field, hole cross, thiopental sodium-induced hypnosis and elevated plus maze test. Present data shows that the organic extracts of G. densiflorum root increase the thiopental sodium induced sleeping time and reduce the time for the onset of sleep. A statistically significant reduction in motor activity and exploratory behavior were observed in the open field and hole cross tests. The results of the current studies provide scientific evidence for its uses in traditional medicines as sedative and anxiolytic agents.